Effects of Group Work to Improve Sophomore Students’ Speaking Skill in English Department of Education Faculty at Balkh University - Sayedi, Pohandoi Shugofa; Ayoobi, Pohanmal Nooria (Integrated Journal for Research in Arts and Humanities, 2024)
The aim of this study is to investigate the significance of using group work to improve sophomore students’ speaking skill in English Department of Education Faculty at Balkh University. The present work is mainly attempts to investigate the students’ awareness of the important of speaking skills in learning English. The results of this study show that most of the students think that speaking is difficult for them because of the lack of real practice. They all agreed that cooperative group working will help them to talk more in a speaking class. The findings of this research show evidence that group work in a good method for developing sophomore students’ speaking skill and increase their classroom oral participation in interactional environment.